Sistem Pemesanan Kopi : Coffee Chill - Andi Dio Nurul Awalia; Fadilah Husnul Khatimah; Azzah Ulima Rahma; Muhammad Raihan (Sakura Digital Nusantara, 2024)
The advancement of technology has made the coffee industry require an effective information system to support marketing and the growth of the coffee chain. The purpose of this research is to develop a web-based ordering information system for coffee shops, called Coffee Chill. This system is designed to provide a practical and enjoyable ordering experience through a user-friendly interface, as well as real-time ordering without queues. This research utilizes interviews and observations as methods to collect data, as well as the Waterfall system development method which includes planning, analysis, design, implementation, and maintenance stages. The planning stage involves analyzing user needs and assessing technical and organizational feasibility. The analysis stage identifies system problems and needs, while the design stage develops system models and architecture. Testing using White Box and Black Box methods is conducted to verify system performance according to specifications. The test results show that this system is highly suitable for development and can improve service and operational efficiency in coffee shops.